2011
DOI: 10.1093/jeg/lbr023
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of the manufacturing belt: determinants of U.S. industrial location, 1880–1920

Abstract: The version presented here is a working paper or pre-print that may be later published elsewhere. If a published version is known of, the above WRAP url will contain details on finding it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 48 publications
(35 reference statements)
1
62
1
1
Order By: Relevance
“…He suggested that if spatial clusters occur within sectors, home bias might be observed because intra-sector trade of intermediate products might take place in these clusters within states even though the distribution of the consumption of final goods was fairly even and not subject to 'excessive' local trade. Klein and Crafts (2012) showed that linkage effects and scale effects were major reasons for the existence of the Manufacturing Belt, which led to the spatial clustering of production of final goods that were purchased nationwide. In this case, we might expect that home bias would be negative, that is, production would be more spatially concentrated than sales of the final good.…”
Section: Spatial Concentration and Home Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…He suggested that if spatial clusters occur within sectors, home bias might be observed because intra-sector trade of intermediate products might take place in these clusters within states even though the distribution of the consumption of final goods was fairly even and not subject to 'excessive' local trade. Klein and Crafts (2012) showed that linkage effects and scale effects were major reasons for the existence of the Manufacturing Belt, which led to the spatial clustering of production of final goods that were purchased nationwide. In this case, we might expect that home bias would be negative, that is, production would be more spatially concentrated than sales of the final good.…”
Section: Spatial Concentration and Home Biasmentioning
confidence: 99%
“…The industrialization of the U.S. economy in the second half of the 19th century brought about a divergence in regional specialization. In manufacturing, regions became highly specialized and by the turn of the 20th century, most of manufacturing employment was concentrated in the regions of New England, Middle Atlantic and East North Central, later labelled the 'Manufacturing Belt' (Fritz, 1943;Perloff et al, 1960;Meyer, 1983Meyer, , 1989Kim and Margo, 2004;Holmes and Stevens, 2004;Klein and Crafts, 2012). This pattern was sustained until the 1940s, after which the degree of regional specialization declined (Kim, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Following a similar approach, Klein and Crafts (2009) have recently questioned some of the conclusions obtained by Kim (1995) for the US 2 . In this case, the analysis was focused on the years between 1880 and 1920 in an attempt to explain the emergence of the US manufacturing belt.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the increasing interest of economic historians in economic geography has been mainly focused on the manufacturing sector (Kim, 1995, Wolf, 2007, Martínez-Galarraga, 2012, Klein and Crafts, 2012. Agriculture is occasionally involved in the analysis, but it merely does so as an exogenous determinant of income, with industry generally still being the main subject of interest (Rosés et al, 2010, Combes et al, 2011.…”
Section: Analytical Framework: Access To Markets and Spatial Patternsmentioning
confidence: 99%